Boundedness of the Solutions to Certain Delay Dynamic Integrodifferential Systems on Time Scales - Min Fan; Yazhou Tian (Discrete Dynamics in Nature and Society)
In this paper, the bounds on the solutions of certain delay dynamic integrodifferential systems on time scales are considered. Based on a new Gronwall-Bellman type delay integral inequality, we can estimate the boundedness of solutions to integrodifferential systems. At the end, an example is presented to state the main results.